A native-visitor in Western Australia: an account of an insider-outsider. Issue 4 (5th October 2015) - Arch G. Woodside, Professor; Holmes, Kirsten; Rowley, Steven
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This study aims to apply confirmatory personal introspection (CPI) to illuminate the experiences of the authors as partial native-visitors to Western Australia. The native-visitor is the tourist who is able to see beyond Urry's shallow conception of the Tourist Gaze through their lengthy immersion as "insiders" in the destination's culture. In this paper, the experiences of two immigrants, the authors, to Western Australia illustrate the different perspectives of the Tourist Gaze 4.0. Design/methodology/approach – The paper uses CPI, as this is a more reliable method of uncovering a traveler's experiences than subjective personal introspection because CPI uses additional data sources such as written historical records and photographs for confirming the researcher's accounts. In this study, accounts of both authors alongside photographs are used to both confirm and contrast their individual experiences. Findings – The paper demonstrates the varied forms of the tourist gaze, with an emphasis on that of the native visitor. The findings illustrate how individuals' both maintain aspects of their original cultural identity and adopt those of the new country after an extended time living in that country. This enables individuals to see attractions and destinations from an insider perspective. Practical implications – This study shows how even after an extended period of time living in a new country, visitors may not have the cultural confidence to behave as local residents at tourist attractions and destinations, which could limit their engagement and enjoyment of these experiences. Marketers should take this into account in designing and promoting tourist experiences to visitors. Originality/value – CPI provides a valuable means for illustrating the range of perspectives within the Tourist Gaze 4.0. The method enables individuals' rich experiences to be uncovered but at the same time uses multiple data sources to provide additional rigour.